2016
DOI: 10.1093/pm/pnw083
|View full text |Cite
|
Sign up to set email alerts
|

Personal Distress and Sympathy Differentially Influence Health Care Professional and Parents’ Estimation of Child Procedure-Related Pain

Abstract: The current findings highlight the important role of caregivers’ felt personal distress when faced with child pain, rather than sympathy, in influencing their pain estimates. Potential implications for pain management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A similar relationship has been found when considering the caregiver's perspective. During lumbar punctures and/or bone marrow aspirations, higher anticipatory caregiver distress was linked to caregivers subsequently reporting higher proxy ratings of the child's pain intensity [64].…”
Section: Concordance and Discordance Between Various Dimensions Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar relationship has been found when considering the caregiver's perspective. During lumbar punctures and/or bone marrow aspirations, higher anticipatory caregiver distress was linked to caregivers subsequently reporting higher proxy ratings of the child's pain intensity [64].…”
Section: Concordance and Discordance Between Various Dimensions Of Thmentioning
confidence: 99%
“…It has been suggested that clinician acute pain treatment decisions are typically based on the presumed mechanism of the pain, previous pain medication use, and clinician experience [3], and there has been little, if any, attention devoted to how best to integrate functional measures, behavioral observations, and children's self-report with such factors. One study found that clinician estimations of a child's procedural pain intensity were influenced by the child's diagnosis, the child's pain behaviors and the clinician's own distress in the anticipatory phase, with higher clinician distress predictive of greater subsequent pain intensity ratings [64]. Although not directly assessed, it was speculated by Caes et al [64], that these factors may, in turn, impact on clinician pain management decisions.…”
Section: Multidimensional Pain Assessment and Therapeutic Decision-mamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these findings emerged despite the quasiexperimental work that found parents rate infants' behaviours as most important for formulating their pain judgements (8). A more recent study by Caes and colleagues (9) examined the influence of caregiver anticipatory distress on caregivers' estimates of their children's pain (ages 0 to 15). The results indicated that higher levels of caregiver distress in anticipation of their child's procedure were related to higher estimations of their child's pain.…”
mentioning
confidence: 99%
“…A number of studies have shown that parental anxiety predicts child procedural anxiety and pain experience from infancy to adolescence (10,11). Particularly, higher parental anxiety is related to less caregiver sensitivity as well as greater anxiety in infants and young children (6)(7)(8)(9)(10)(11)(12) years of age), suggesting parents are less available to help their child regulate if they are not regulating their own emotions (11,12,13). A recent study revealed that preschoolers' procedural anxiety mediates the relationship between parents' anticipatory anxiety and children's procedural pain (14).…”
mentioning
confidence: 99%